A Comparative Study of Teachers’ Pedagogical Competencies in Supporting Children with Learning Difficulties in Primary Schools in Ghana and Brunei Darussalam - Abosi, Okechukwu; Alhassan, Abdul Razak Kuyini (Journal of the American Academy of Special Education Professionals, 2017)
Teachers’ pedagogical competencies level is increasingly affecting the implementation of inclusive education policy in many countries. The aimed at comparing primary school teachers’ competence levels in supporting children with learning difficulties in Brunei Darussalam and Ghana. Descriptive survey design was used and 188 primary school teachers from Brunei Darussalam and Ghana participated in the study. Results showed that teachers from Brunei Darussalam and Ghana had limited to moderate competencies in supporting children with learning difficulties in the general education classroom. In addition, the results showed that there was no significant difference between the competence level of teachers in Brunei Darussalam and Ghana. It is recommended both countries must work towards improving their teachers’ competencies in curriculum adaptation, instructional strategies, identification and assessment of children disabilities and their skills in collaboration.